Interactive Assessment Tools for Computational Thinking in High School STEM Classrooms - Weintrop, David; Beheshti, Elham; Horn, Michael S.; Orton, Kai; Trouille, Laura; Jona, Kemi; Wilensky, Uri (Intelligent Technologies for Interactive Entertainment, 2014)
This paper presents a pair of online, interactive assessments designed to measures students’ computational thinking skills. The assessments are part of a larger project to bring computational thinking into high school STEM classrooms. Each assessment includes interactive tools that highlight the power of computation in the practice of scientific and mathematical inquiry. The computational tools used in our assessments enable students to analyze data with dynamic visualizations and explore concepts with computational models.